Demographic implications of transiting from segregation to integration: a focus on education issues in Buffalo City, South Africa - Siyongwana, Pakama; Chanza, Nelson (Bulletin of Geography. Socio-economic Series, 2020)
The study aims at interrogating the transformation of education in Buffalo City following integration of East London with its black townships. This paper is largely framed from a quantitative paradigm that draws from statistical data in linking population changes with educational patterns in the study area. Census data was used to trace population changes in post-apartheid South Africa, while performance in education was informed by matriculation results. Quantitative data were complemented with key informants’ qualitative opinions. The results indicate that the quality of education in former “white” schools is better than that of “township” schools. There are several pull factors that attract township learners to former white schools, albeit with integration challenges. The study concludes that if these challenges are masked to education planners and policy makers, they militate against the envisioned liberalisation of the democratic education system.